Effect of Different Level of GA3 on Growth and Yield of Cabbage - Roy, R; Nasiruddin, KM (Journal of Environmental Science and Natural Resources, 2012)
The research work was conducted to study the effect of GA3 on growth and yield of cabbage. Single factor experiment consisted of four concentrations of GA3, viz., 0, 25, 50 and 75 ppm. Significantly the minimum number of days to head formation (43.54 days) and maturity (69.95 days) was recorded with 50 ppm GA3 and 50 ppm GA3 gave the highest diameter (23.81 cm) of cabbage head while the lowest diameter (17.89 cm) of cabbage head was found in control (0 ppm GA3) treatment. The application of different concentrations of GA3 as influenced independently on the growth and yield of cabbage. Significantly the highest yield (45.22 kg/plot and 104.66 t/ha) was found from 50 ppm GA3. DOI: http://dx.doi.org/10.3329/jesnr.v4i2.10138 J. Environ. Sci. & Natural Resources, 4(2): 79-82, 2011